Current developments in algebraic geometry - Caporaso, Lucia (Mathematical sciences research institute publications, 2012)
"1. Introduction Let X c Pr be a smooth projective variety of dimension n over an algebraically closed field k of characteristic zero, and let n : X -" P"+c be a general linear projection. In this note we introduce some new ways of bounding the complexity of the fibers of jr. Our ideas are closely related to the groundbreaking work of John Mather, and we explain a simple proof of his result [1973] bounding the Thom-Boardman invariants of it as a special case"--